Are fish oil-based dietary supplements a significant source of exposure to chlorinated paraffins? - Tomasko, Jakub; Hrbek, Vojtech; Kourimsky, Tomas; Stupak, Michal; Hajslova, Jana; Pulkrabova, Jana (The Science of the total environment, 2022)
Chlorinated paraffins (CPs) are an emerging group of environmental pollutants associated with adverse effects on human health (such as endocrine disruption and possible carcinogenicity). CPs are classified into several groups: short- (SCCPs), medium- (MCCPs) and long-chain chlorinated paraffins (LCCPs). In this study, CPs were determined in fish oil-based omega-3 dietary supplements (DS) representing widely consumed products that might be contaminated with various lipophilic contaminants including CPs. The CPs were isolated from DS (n = 85) by solid phase extraction. The SCCPs and MCCPs were determined by gas chromatography coupled with high-resolution mass spectrometry operated in a negative chemical ionisation mode. The LCCPs (up to C21) were screened using supercritical fluid chromatography coupled with high-resolution mass spectrometry with electrospray ionisation operated in negative mode. The CP concentrations varied from <0.01 to 56.48 μg/g fat for SCCPs (median 0.12 μg/g fat; limit of quantification, LOQ, for SCCPs was exceeded in 51 out of 85 samples) and from <0.03-89.08 μg/g fat for MCCPs (median 0.26 μg/g fat; LOQ for MCCPs was exceeded in 66 out of 85 samples), respectively. The LCCPs were not quantified in this study, nevertheless their limit of detection (0.5 μg/g fat) was exceeded in 7 out of 85 samples. Due to high levels of CPs, DS might pose as a significant source of CPs exposure to some population groups.
Keywords: parafín; Dietary exposure estimation; Dietary supplements; dietní tuky nenasycené; chlorované uhlovodíky; Čína; Environmental Monitoring; Hydrocarbons, Chlorinated; Chlorinated paraffins; High resolution mass spectrometry; China; Dietary Fats, Unsaturated; rybí oleje; Supercritical fluid chromatography; monitorování životního prostředí; Paraffin; plynová chromatografie s hmotnostně spektrometrickou detekcí; potravní doplňky; Dietary Supplements; Fish Oils; Gas Chromatography-Mass Spectrometry; Gas chromatography